Nutritional status and weight gain in Peruvian pregnant women, 2009-2010 - Tarqui Mamani, Carolina (2014)
Introduction: Pregestational maternal nutritional status and weight gain during pregnancy affect maternal and perinatal conditions and increases the risk of low birth weight, preterm birth and perinatal maternal mortality. Objectives: To determine nutritional status and weight gain of Peruvian pregnant women. Design: Cross-sectional observational study conducted during 2009-2010 in Peru. Setting: National Institutes of Health, Lima, Peru Participants: Pregnant women residing in Peruvian households. Interventions: The sample was probabilistic, stratified, multistage and independent in each department. From the sample of 22 640 households 552 pregnant women were included. Anthropometric measurements were performed according to international methodology. Nutritional status and weight gain during pregnancy were obtained by using pre-pregnancy bone mass index according to the Institute of Medicine of USA. Main outcome measures: Nutritional status and weight gain during pregnancy. Results: It was found that 1.4% of pregnant women began pregnancy underweight, 34.9% had normal weight, 47% were overweight and 16.8% had obesity. During pregnancy 59.1% showed low weight gain, 20% normal weight gain and 20.9 % excessive weight gain. More pregnant women were overweight and obese, lived in urban areas and were not poor. Conclusions: More than half of Peruvian pregnant women began pregnancy overweight or obese and most had insufficient weight gain during pregnancy.